2020
DOI: 10.1002/pro.3839
|View full text |Cite
|
Sign up to set email alerts
|

Miro: A molecular switch at the center of mitochondrial regulation

Abstract: The orchestration of mitochondria within the cell represents a critical aspect of cell biology. At the center of this process is the outer mitochondrial membrane protein, Miro. Miro coordinates diverse cellular processes by regulating connections between organelles and the cytoskeleton that range from mediating contacts between the endoplasmic reticulum and mitochondria to the regulation of both actin and microtubule motor proteins. Recently, a number of cell biological, biochemical, and protein structure stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 112 publications
(185 reference statements)
1
35
0
Order By: Relevance
“…The Miro1 protein is localized to the outer membrane of mitochondria [ 28 ]. Miro1, and the related Miro2 protein, promote anterograde trafficking of mitochondria by interacting with proteins that bind to microtubule motors and the actin cytoskeleton [ 29 ]. Miro1 is also required for symmetrical inheritance of mitochondria during cell division [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Miro1 protein is localized to the outer membrane of mitochondria [ 28 ]. Miro1, and the related Miro2 protein, promote anterograde trafficking of mitochondria by interacting with proteins that bind to microtubule motors and the actin cytoskeleton [ 29 ]. Miro1 is also required for symmetrical inheritance of mitochondria during cell division [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential roles of enzymatic activity in these catalytically active pseudoGTPase domains are still in question, with the GTPase activity of N‐GTPase thought to be required for proper Miro function in mitochondria but the C‐GTPase activity to be dispensable [46,49,50]. These GTPase‐like domains have been suggested to affect mitochondrial processes via allosteric regulation of target proteins, but the specific targets and mechanisms have not yet been fully determined [51].…”
Section: Members Of the Pseudogtpase Groupmentioning
confidence: 99%
“…The Miro GTPases are a family of tail-anchored proteins, localised in the outer mitochondrial membrane with two calcium binding EF-hand domains and an N-and C-terminal GTPase domain residing in the cytoplasm [54,55]. Work since the discovery of this family [54] has shown that Miro has a broad impact on mitochondrial homeostasis, distribution, morphology, ER-mitochondria contact sites, calcium buffering and mitophagy [56][57][58][59][60][61][62][63][64][65][66][67]. The best characterised of these roles is in regulating mitochondrial distribution through long range, microtubule-dependent mitochondrial transport [38,68].…”
Section: The Role Of Miro Gtpases In Mitochondrial Transportmentioning
confidence: 99%
“…There are four other important considerations regarding any overlap in mitochondrial and peroxisomal transport. Firstly, Miro is near ubiquitous to eukaryotic life and is observed to have a diverse range of roles in mitochondrial homeostasis [ 56 , 91 , 92 ]. Consequently, Miro is not only a trafficking protein and, therefore, other roles for Miro at peroxisomes should be considered.…”
Section: The Impact Of the Miro Gtpases On Peroxisomesmentioning
confidence: 99%